Tingkat Walkability dan Kepuasan Pejalan Kaki di Kawasan Pendidikan Jatinangor dan Kawasan Perdagangan Sudirman - Vitalani Rahmatiani; Byna Kameswara (TATALOKA, 2021)
Walkability is a condition in an area that is friendly to pedestrians. To find out the comparison of the conditions of the pedestrian path, 2 (two) areas with different land uses but having the same characteristics are high pedestrians and problems related to walkability that have not been resolved. This study aims to identify the differences between the two research areas and the level of satisfaction of pedestrian users using the Global Walkability Index. The Jatinangor Education Area has a value of 45.5 which means not walkable, while the Sudirman Commercial Area has a value of 60.0 which means waiting to walk. Pedestrians show their dissatisfaction walking in the Jatinangor Education Area and pedestrians show their satisfaction in the Sudirman Commercial Area. This indicates that the Sudirman Commercial Area is more walkable than the Jatinangor Education Area. The results of the research are expected to serve as a direction for the development of the built environment's capacity to achieve a walkable area